Variasi Bahan Pakaian Dan Kejadian Keputihan: Variations in Clothing Materials and the Occurrence of Vaginal Discharge - Rukmana, Sitti (Jurnal Abdi Keperawatan dan Kedokteran, 2022)
Leucorrhoea is a symptom that is very often experienced by most women. Material clothing can cause vaginal discharge. The material from the underwear is also quite crucial in influencing the risk of vaginal discharge. The aim is to determine the relationship between the use of clothing materials and vaginal discharge at the STIE Mujahidin Tolitoli. The design used in the study was Cross Sectional. The population is all young women. The sample size is 30 respondents using Random sampling technique. Independent variables of the study are variations in clothing types. The dependent variable is the event of vaginal discharge. Data was collected using a questionnaire, then the data were analyzed using Chi square test with a significance level of α ≤0.05. The results showed that almost half of the respondents had 12 types of cotton clothing (40%), leucorrhoea had 19 respondents (63.3%). The results obtained a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected which means that there is a relationship between Variations in the Use of Clothing Material and Leucorrhoea Events at STIE Mujahidin Tolitoli There is a Relation of Variations in the Use of Clothing Materials and Leucorrhoea Events at STIE Mujahidin Tolitoli. The right type of material will minimize the incidence of vaginal discharge and health.